PENGARUH MODEL PICTURE AND PICTURE BERBANTUAN MEDIA PUZZLE TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 3 BELEKA TAHUN PELAJARAN 2018/2019 - Marniati Marniati; Ahmad Harjono; Ida Ermiana (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2020)
This study is an experimental research which aims to determine the effect of learning model of picture and picture use media puzzle on the learning outcomes of science students of grade V SDN 3 Beleka sub district in academic year of 2018/2019. The method used in this research is quasi experimental design with the design nonequivalent control group design. The sampling technique used is non-probability sampling such as saturated sampling. Population in this research are 66 students of class V SDN 3 Beleka, the VA class student as experiment class and the VB as control class. The learning result data (posttest) was tested for normality with chi-square and then tested its homogeneity using the largest variance ratio and the smallest variance, the test showed that the data were normal and homogeneous distributed. Furthermore, the data were analyzed by using the t-test (separated variance). obtained tcount of 3,43 and ttable of 1.9987 with 5% significant level. The explanation shows that thitung is bigger than ttable so it can be concluded that Ha is accepted and H0 is rejected. This shows that there is influence of learning model of picture and picture use media puzzle on the learning outcomes of science students of grade V SDN 3 Beleka academic year 2018/2019.